Contribuição ao estudo da sustentabilidade sob a ótica da gestão econômica: uma análise do relatório de sustentabilidade - Daud, Rodrigo Kaltbeitzer (2013)
The present study aimed to analyze the sustainability report 2011 of the companies surveyed, in order to verify that the information contained in this report are presented effectively for aspects and concepts surveyed regarding the topics Sustainability and Sustainable Management. The option to restrict the search firms that participated in the Corporate Sustainability Index (ISE) in 2011 of the BM&FBovespa, was due to the complexity of the issues Sustainable Development and Sustainability, as well as the perception that companies in general are still in full conceptual discussion as to its breadth, approach and application in business. Data analyzed and used for this study were drawn from extensive literature search on the topic and the official website of the company object of this research. Finally, it was observed that the sustainability reports of companies surveyed in 2011, were not detected information effectively on the economic result of actions arising from sustainability, in accordance with the definitions of this research